Causation in Marine Insurance: The Conflicts between Perils of the Sea and the Exclusions (Journal of Governance and Development (JGD), 2009)
The law of Marine Insurance, unlike any other areas of commercial law, is yet to be prevalently known in Malaysia and to this date, Malaysia is yet to have its very own legislations in marine insurance. Due to such lacunae, the Malaysian courts have to look into the English law (i.e. the Marine Insurance Act 1906). Under a contract of marine insurance, as in any other contract of insurance, the question of proximate cause of a loss plays an important role in order to determine what causes a particular loss: an insured or excluded peril. In practice, the question of causation normally appears when the question of perils of the sea arises. A peril that qualifies to be enumerated under the expression â€œperils of the seaâ€ must be one that has both the elements of fortuity and unexpectedness. Although there are established perils enumerating the expression â€œperils of the seaâ€, which have relatively outlined the limits of perils of the sea, its parameter is still subject to further study. It is also pertinent to look into the area of excluded perils in order to assist the effort to determine the extent and limit of perils of the sea. The excluded perils under marine insurance come under two broad categories: the statutory exclusions expressly provided for under Section 55 (2) of the English Marine Insurance Act 1906 and the contractual exclusions referring to the marine policy contracted between the assured and the underwriter. Thus, this paper attempts to look into the dichotomies between perils of the sea and some of the excluded perils, with the purpose of determining a clearer and definitive parameter of perils of the sea.